2022
DOI: 10.1007/s12192-022-01290-0
|View full text |Cite
|
Sign up to set email alerts
|

HSP70 protects H9C2 cells from hypoxia and reoxygenation injury through STIM1/IP3R

Abstract: Hypoxia/reoxygenation (H/R) is used as an in vivo model of ischemia/reperfusion injury, and myocardial ischemia can lead to heart disease. Calcium overload is an important factor in myocardial ischemia–reperfusion injury and can lead to apoptosis of myocardial cells. Therefore, it is of great clinical importance to find ways to regulate calcium overload and reduce apoptosis of myocardial cells, and thus alleviate myocardial ischemia–reperfusion injury. There is evidence that heat shock protein 70 (HSP70) has a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…IP3R is a key regulator of SBP and contractility of VSMCs (53). Upregulation of IP3R is associated with hypoxia and reoxygenation-induced cardiomyocyte injury (54). According to our results, CEBPD enriched on the miR-96-5p promoter, and the binding relationships between CEBPD and miR-96-5p, miR-96-5p and IP3R were further verified by the dual-luciferase assay.…”
Section: Discussionmentioning
confidence: 99%
“…IP3R is a key regulator of SBP and contractility of VSMCs (53). Upregulation of IP3R is associated with hypoxia and reoxygenation-induced cardiomyocyte injury (54). According to our results, CEBPD enriched on the miR-96-5p promoter, and the binding relationships between CEBPD and miR-96-5p, miR-96-5p and IP3R were further verified by the dual-luciferase assay.…”
Section: Discussionmentioning
confidence: 99%
“…Elevation of complement C3 in the liver of Eurasian perch, an important central component of the immune system, was induced by hypoxia, suggesting that the quantity and activity of complement system proteins are changed by a single hypoxia shock (Douxfils et al ., 2012). Recent studies (Liu et al ., 2022; Salnikow et al ., 2002; Zhang et al ., 2016) indicated that Ca 2+ was related to the cellular reaction of lower oxygen stress, and the free intracellular Ca 2+ of endothelial cells increased significantly after 2 h of hypoxia stress. Therefore, hypoxia can initiate many cascade reactions to help organisms adapt to lower oxygen conditions.…”
Section: Introductionmentioning
confidence: 99%